Attitude of medical doctors to adverse drug reactions reporting in Bulgaria - Dobriana Sidjimova; Tatyana Benisheva; Vili Topalova; Valentina Petkova (Pensoft Publishers, 2024)
Adverse Drug Reactions (ADRs) pose a challenge for medical doctors (MDs) and other healthcare professionals (HCPs). Serious ADRs increase patient morbidity and mortality and generate a large financial footprint on healthcare costs. Statistics show that about 6% of hospitalizations are due to ADRs and over 50% of them could be avoided. Two years after introducing the pharmacovigilance (PhV) requirements in the European Union, national regulatory PhV requirements were published in the Bulgarian pharmaceutical legislation. Nonetheless, MDs' awareness of the PhV topic still remains extremely important due to patient safety. Spontaneous reporting of ADRs is essential to the success of a pharmacovigilance program. Underreporting of ADRs is common, especially among MDs and HCPs. This study aims to analyse the attitude and the knowledge of graduated MDs towards the reporting of ADRs and drug safety in general. In addition, the study aims to examine their opinion, attitude, and recommendations so that reporting of ADRs becomes more regular.